This research objective was to evaluate the physical and mechanical properties of particleboard made from logging residue from plantation forest, namely akasia (Acacia mangium) and ekaliptus (Eucalyptus sp). Type particle was sawdust and bonded with Urea Formaldehyde (UF)-Isocyanate mix resin with ratio 100:15. Control resin (UF) was also prepared for comparison with resin solid content 52.7%. The target thickness of particleboard was 1 cm, pressed at 25 kg/ cm2 for 15 minutes at 140 °C. Level o - Arif NURYAWAN; Iwan RISNASARI; Pamona Silvia SINAGA (Jurnal Ilmu dan Teknologi Hasil Hutan, 2009)
This research objective was to evaluate the physical and mechanical properties of particleboard made from logging residue from plantation forest, namely akasia (Acacia mangium) and ekaliptus (Eucalyptus sp). Type particle was sawdust and bonded with Urea Formaldehyde (UF)-Isocyanate mix resin with ratio 100:15. Control resin (UF) was also prepared for comparison with resin solid content 52.7%. The target thickness of particleboard was 1 cm, pressed at 25 kg/ cm2 for 15 minutes at 140 °C. Level of resin was 7% based on oven dry particle weight. The boards were evaluated based on JIS A 5908-2003. The results showed:1) Utilization of               UF-isocyanate mix resin improved the moisture content, thickness swelling, and water absorption of particleboard 2) The best particleboard from physical and mechanical properties point of view was particleboard made of akasia bonded with UF-isocyanate mix resin   Keywords :  Physical and mechanical properties, logging residue, particleboard